Implementation of Project Based Learning Model To Improve Students' Learning Outcomes in Islamic Cultural History Learning at MAN 3 Blitar - Ustafidah, Wiji; Warta; Wardaniyah; Jaelani, Uus; Wahydin (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to determine the effectiveness of the implementation of the Project Based Learning (PBL) learning model in improving student learning outcomes in the Isra' Mi'raj material in the subject of Islamic Cultural History (SKI) class XB MAN 3 Blitar. PBL was chosen as a learning model because it is considered capable of increasing student activity and creativity through projects that are relevant to the subject matter. The research method used is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of 1 of planning, implementation, observation, and reflection. The subjects of the 2 studies were 30 students of class XB MAN 3 Blitar. Data were collected through learning outcome tests, observation of student activities, and project documentation. The results showed that the implementation of the PBL model succeeded in improving student learning outcomes in the Isra' Mi'raj material. This can be seen from the increase in the average score of student learning outcome tests from cycle I to cycle II. In addition, student activity and creativity in the learning process also increased. Students appear more enthusiastic and active in working on the projects given. The conclusion of this study is that the implementation of the PBL model is effective in improving student learning outcomes in the Isra' Mi'raj material of the SKI subject for class XB MAN 3 Blitar. The PBL model can be an interesting and effective learning alternative to improve students' understanding of the subject matter.